Analisis Praktik Berbagi Pengetahuan Menggunakan Model SECI: Studi Kasus Kualitatif di Perpustakaan Universitas Negeri Gorontalo - Nadia Safitri Suleman; Moh. Hidayat Koniyo; Lillyan Hadjaratie; Muhammad Rifai Katili; Indhitya R. Padiku; Sri Nilawaty Lahay (Universitas Sebelas Maret Library, 2026)
This study analyzes knowledge-sharing practices at the Gorontalo State University Library using the SECI model (Socialization, Externalization, Combination, Internalization) through a qualitative approach. The study involved 7 informants, all of whom were librarians. The data analysis technique used was thematic analysis, which involved the stages of data reduction, data presentation, and drawing conclusions. The results show that the four SECI stages have been implemented with varying degrees of effectiveness. Socialization takes place through informal discussions, training, and the use of social media. Externalization is carried out through knowledge documentation and the writing of scientific papers. A combination is evident in the management of explicit knowledge through the SLIMS system, OPAC, and repositories. Meanwhile, internalization is carried out through training that is still dominated by online methods. The main findings indicate that knowledge-sharing practices are not yet optimal, particularly at the internalization stage, which remains limited to online training, and at the externalization stage, which has not been implemented uniformly. Supporting factors include leadership and the use of technology, while the main barriers are limitations among librarians and technical challenges. This study contributes to providing an empirical overview of the implementation of the SECI model in university libraries and serves as a foundation for strengthening a culture of knowledge sharing.